Dynamic of Teacher-Student Interaction in Fastering an Engaging Learning Environment Towards Students’ Participation and Happiness - Wildatulrahmah; Karimuddin; Syarif Hidayat Nasir; Roslina; Susi Astiantih (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the dynamics of teacher–student interactions and their impact on student engagement and happiness in the learning process at SMA Negeri 1 Tirawuta, Indonesia. In recent years, positive communication and emotional support in classroom settings have become increasingly important in fostering engaging and enjoyable learning environments, particularly at the secondary school level. This study employed a qualitative descriptive design involving seven teachers selected through a purposive sampling technique. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify patterns of interaction, instructional strategies, and emotional dynamics influencing students’ participation in learning activities. The findings reveal that positive teacher–student interactions,such as emotional support, the use of open-ended questions, collaborative group discussions, and formative assessment practices play a crucial role in enhancing student participation, emotional comfort, and happiness in the classroom. In this study, qualitative engagement refers to students’ meaningful involvement in learning processes, reflected through active participation, emotional responsiveness, and a sense of psychological safety. However, several challenges were also identified, including differences in students’ academic abilities, limited school facilities, and low levels of student self-confidence, which hinder the effectiveness of interactive learning practices. This study concludes that responsive communication, adaptive instructional strategies, and sustained emotional support are essential components in creating a supportive and engaging learning environment. The findings contribute theoretically by enriching the discourse on teacher–student interactions through an emotional perspective and practically by providing insights for teachers and school stakeholders to integrate emotional aspects into classroom interaction practices to enhance student engagement and well-being.